TASKS DESIGNED TO PROVIDE CLASSROOM ACTIVITIES BASED ON 2013 CURRICULUM: A CONTENT ANALYSIS OF ENGLISH TEXTBOOK PATHWAY TO ENGLISH - Vitaresti, Mungki (Jurnal Penelitian Humaniora, 2015)
This study is mainly intended to find out the tasks type in Pathway to English textbook which are designed to provide classroom activities based on five learning cycles as the basic of 2013 curriculum. The objective of this research is to identify the suitability of the labeled tasks design in Pathway to English with the relevant theory of five learning cycles in scientific approach, namely: observing, questioning, exploring, associating, and communicating activities. This study is qualitative research which involves content analysis approach. The object of this research is the tasks in English textbook Pathway to English for the tenth grade of Senior High School written by Th. M. Sudarwati and Eudia Grace published by Erlangga in 2013. In collecting the data, the researcher uses documentation technique. The data are analyzed using Creswellâs theory. The study reveals that not all task types in textbook are relevant to five learning cycles of CurriculumÂ 2013. The result shows that 59.4% task types are relevant to scientific approach, whileÂ 40.6% task types are irrelevant to scientific approach. Considering the result above, itÂ can be concluded that the tasks design in Pathway to English are not sufficient to provide students activities and cannot measure entire studentsâ knowledge, skill and attitude as the important competence in 2013 curriculum.